Effects of green operational practices and e-CRM on patient satisfaction among Indonesian hospitals: exploring the moderating role of green social influence - MS, Mahrinasari; Haseeb, Muhammad; Bangsawan, Satria; Sabri, Mohamad Fazli; Mohd Daud, Norzaidi (Regional Association for Security and Crisis Management, 2023)
This study aims to investigate the implementation of environmentally friendly operational practices in the healthcare industry. Green operational practices or sustainable practices are acquiring widespread attention in manufacturing and other production-related industries. However, its application in the healthcare sector is still in its infancy, making this study an important addition to the existing body of knowledge, as very few studies have previously investigated the role of green operational practices in a healthcare context. The study analyzed the role of green building, eco-design, green supply chain, and green innovation in determining patient satisfaction by analyzing data collected from hospital administration and patients in Indonesia. All four dimensions of green operational practices positively correlate with patient satisfaction. In addition, the study discovered a correlation between E-CRM practices and patient satisfaction. In addition, the moderating role of green social influence was examined and found to be a positive moderator in the relationships between all four dimensions okokof green operational practices and patient satisfaction, as well as the relationship between E-CRM and patient satisfaction. The study's findings provide valuable insights into the management of the healthcare sector.